Carissa edulis Vahl (Apocynaceae) extract, a medicinal plant of Benin pharmacopoeia, induces potent endothelium-dependent relaxation of coronary artery rings involving nitric oxide - TOKOUDAGBA, Kossi Jean-Marie Denis; VILLETTE, CLAIRE; Houngue, Ursula (My University, 2022)
Hypertension is a major cardiovascular risk factor that affects most countries including those of Africa. Although Carissa edulis Vahl, Diodia scandens Sw. and Cleome gynandra L. are traditionally used in Benin as antihypertensive treatments with some efficacy mentioned by the local population, their biological activity on the cardiovascular system remains poorly studied. Aim: The study investigated the vasoreactivity of the plants and assessed the underlying mechanisms using isolated arteries. Study design: Aqueous-ethanolic extracts of aerial parts of C. edulis, D. scandens and C. gynandra were prepared by maceration before being subjected to multi-step liquid-liquid fractionation with solvents of increasing polarity. The vasoreactivity of the extracts and fractions were assessed on isolated porcine coronary artery and rat aorta using organ chambers, the role of nitric oxide (NO) using NG-nitro-L-arginine (NO synthase inhibitor), prostanoids using indomethacin (cyclooxygenases inhibitor) and endothelium-dependent hyperpolarization using TRAM-34 plus UCL 1684 (inhibitors of calcium-dependent K+ channels), and the vascular uptake of polyphenols using Neu reagent. Results: The aqueous-ethanolic crude extract of C. edulis (CECE) induced potent relaxations that were exclusively endothelium-dependent and more pronounced than those to D. scandens and C. gynandra. The n-butanolic fraction of C. edulis (CEBF) was more active than the cyclohexane, dichloromethane, and ethyl acetate fractions. The relaxation induced by CECE and CEBF were inhibited by NG-nitro-L-arginine and affected neither by TRAM- 34 plus UCL 1684 nor by indomethacin. CEBF induced sustained endothelium-dependent relaxations for at least 60 min, and inhibited, in a concentration-dependent manner, contractions to KCl, CaCl2, U46619 and serotonin in rings with endothelium. Analysis of CEBF by LC–HRMS indicated the presence of polyphenols, terpenes, and alkaloids. Exposure of coronary artery and aorta rings to CEBF caused the accumulation of polyphenols predominantly in the endothelium. Conclusion: C. edulis leaf extract induced pronounced endothelium-dependent relaxations and inhibited contractile responses by stimulating the endothelial formation of NO. LC–HRMS analysis of the most active fraction, the butanolic fraction, revealed the presence of numerous compounds including polyphenols, terpenes, and alkaloids. The polyphenols of CEBF accumulated preferentially in the endothelium of the arterial wall. Thus, these observations support the folkloric use of C. edulis in hypertension.
Keywords: Hypertension Carissa edulis Endothelium Vasorelaxant activity Nitric oxide